2020
DOI: 10.1111/ane.13370
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐life care in amyotrophic lateral sclerosis: A comparative registry study

Abstract: Background Amyotrophic lateral sclerosis (ALS) is a fatal disease requiring palliative care. End‐of‐life care has been well studied in patients with incurable cancer, but less is known about the quality of such care for patients with ALS. Aim To study whether the quality of end‐of‐life care the last week in life for patients dying from ALS differed compared to patients with cancer in terms of registered symptoms, symptom management, and communication. Design This retrospective comparative registry study used d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Our review included two qualitative studies with interviews [ 20 , 21 ], one RCT [ 22 ], three cohort studies (two retrospective [ 23 , 24 ], one prospective [ 25 ]), and two comparative retrospective chart/registry studies [ 26 , 27 ]. The majority of articles originated from Europe, with contributions from the United Kingdom [ 20 , 21 ], Italy [ 22 ], Finland [ 23 ], Sweden [ 24 , 26 ], and France [ 25 ]. One article was from the United States of America [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review included two qualitative studies with interviews [ 20 , 21 ], one RCT [ 22 ], three cohort studies (two retrospective [ 23 , 24 ], one prospective [ 25 ]), and two comparative retrospective chart/registry studies [ 26 , 27 ]. The majority of articles originated from Europe, with contributions from the United Kingdom [ 20 , 21 ], Italy [ 22 ], Finland [ 23 ], Sweden [ 24 , 26 ], and France [ 25 ]. One article was from the United States of America [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective registry study, Eljas Ahlberg et al compared 825 deceased ALS patients to 3300 deceased cancer patients, examining topics such as symptom assessment, prescription of as-needed drugs, and communication about the transition to end-of-life care [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite an expanding evidence-base on symptom management, patients with NMDs are likely to receive poorer symptom control at the end of life than those dying with cancer. 83 , 84 A recent qualitative study of bereaved carers demonstrated that unmanaged respiratory and psychological symptoms were frequently a significant cause of distress to both patients and their carers. 32 As discussed above, symptoms should be proactively addressed and reviewed regularly.…”
Section: Discussion Of Palliative Care Themesmentioning
confidence: 99%
“…Older age decreased the probability of implementing appropriate palliative measures during the last week of life and involving a specialized palliative team [ 16 , 17 ]. Diagnosis seems also to be of importance as previous studies conclude that a patient who is dying of cancer is more likely to be offered palliative interventions than patients dying of amyotrophic lateral sclerosis [ 18 ], COPD [ 19 ], dementia [ 20 ], or stroke [ 21 ].…”
Section: Discussionmentioning
confidence: 99%